2019
DOI: 10.1038/s41467-019-09578-z
|View full text |Cite
|
Sign up to set email alerts
|

Centromere mechanical maturation during mammalian cell mitosis

Abstract: During mitosis, tension develops across the centromere as a result of spindle-based forces. Metaphase tension may be critical in preventing mitotic chromosome segregation errors, however, the nature of force transmission at the centromere and the role of centromere mechanics in controlling metaphase tension remains unknown. We combined quantitative, biophysical microscopy with computational analysis to elucidate the mechanics of the centromere in unperturbed, mitotic human cells. We discovered that the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…In addition, the mechanisms that correct merotelic attachments are expected to be particularly sensitive to subtle changes in inter-centromeric tension induced by changes in kinetochore microtubule occupancy [ 53 ], and therefore tension defects induced by aberrant chromatin compaction in USP22-depleted cells are likely to impair merotelic error correction. While this possibility remains to be formally evaluated, it is supported by the findings of Harasymiw and colleagues [ 57 ], who determined that altered chromatin stiffness selectively promotes lagging chromosomes but not chromatin bridges in anaphase. Although not all lagging chromosomes are expected to induce chromosome segregation errors, an increase in their abundance is predicted to enhance the probability of chromosome mis-segregation events leading to CIN.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, the mechanisms that correct merotelic attachments are expected to be particularly sensitive to subtle changes in inter-centromeric tension induced by changes in kinetochore microtubule occupancy [ 53 ], and therefore tension defects induced by aberrant chromatin compaction in USP22-depleted cells are likely to impair merotelic error correction. While this possibility remains to be formally evaluated, it is supported by the findings of Harasymiw and colleagues [ 57 ], who determined that altered chromatin stiffness selectively promotes lagging chromosomes but not chromatin bridges in anaphase. Although not all lagging chromosomes are expected to induce chromosome segregation errors, an increase in their abundance is predicted to enhance the probability of chromosome mis-segregation events leading to CIN.…”
Section: Discussionmentioning
confidence: 86%
“…In particular, merotelic attachments (i.e., simultaneous attachment of a kinetochore to both spindle poles) do not activate the SAC and generate lagging chromosomes specifically in anaphase when left uncorrected. As the mechanisms responsible for correction of merotelic attachments may be exquisitely sensitive to subtle tension defects in metaphase [ 53 , 57 , 58 ], impaired chromatin compaction and altered inter-centromeric tension within USP22 -silenced cells may compromise these repair mechanisms, resulting in increased frequency of segregation defects.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the centromeric chromatin spring is more compliant in RPE1 cells than in HeLa cells (Armond et al, 2015), corresponding to lower spring constant, , which is consistent with reduced breathing between sister kinetochores in HeLa cells compared to that in RPE1 cells. Whether stiffer centromeric chromatic springs is typical for cancer cells is unknown, but could explain disrupted centromere mechanical maturation (Harasymiw et al, 2019) in aneuploid cell lines, and recent observations of attenuated chromosome oscillations in cancer cell lines Iemura et al (2021). Similarly, the K-fibres forces − , + have a larger difference in magnitude in RPE1 cells than in HeLa cells, with possible relevance to the increased kinetochore-microtubule dynamics reported in RPE1 cells relative to cancer cell lines (Bakhoum et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Sister kinetochores are capable of maintaining attachment to both growing and shrinking microtubule bundles (K-fibres) that generate pushing and pulling forces on the chromosomes respectively (Armond et al, 2015). Moreover, sister kinetochores are physically connected by centromeric chromatin which behaves as an elastic spring (Stephens et al, 2013;Harasymiw et al, 2019) and enables mechanical cues to be transmitted between kinetochores (Burroughs et al, 2015;Wan et al, 2012). Such cues control directional switching, giving rise to the metaphase oscillatory dynamic (Burroughs et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The centromere, which consists of repetitive DNA, is the region where sister chromatids remain connected until mitosis and has a unique histone-CenpA. The centromere is the 'landing platform' for the kinetochore, a large protein structure that binds to microtubules in mitosis and ensures accurate sister chromatid separation and chromosome segregation [40,41]. Because centromeres lack ecDNA, ecDNA segregates unevenly at cell division, allowing daughter cells to possess up to twice as many ecDNA particles as their corresponding mother cells [31].…”
Section: Ecdna Is Acentric With Uneven Segregation At Cell Divisionmentioning
confidence: 99%